Sariswara dalam dinamika budaya: Analisis nilai budaya dan karakter bangsa - Wachid Pratomo; Sapriya Sapriya; Dadang Sundawa; Susan Fitriasari (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
The Sariswara method, as a form of literary expression that combines elements of story, song, and language, has an important role in shaping and reflecting the values ​​and character of the nation. This article aims to analyze how the sariswara method represents cultural values ​​and good characters that grow and develop in Indonesian society. Through a qualitative approach and content analysis of several sariswara works, it was found that sariswara is not only a means of entertainment, but also acts as a means of transmitting moral values, ethics, the spirit of collectivity (mutual cooperation), and respect for parents, and love for the homeland. In the context of the dynamics of culture that continues to develop, sariswara shows flexibility and relevance in conveying noble messages in a subtle and touching way. This study confirms that the preservation and strengthening of sariswara has a strategic contribution in maintaining cultural identity and shaping the character of the nation, such as integrating values ​​such as honesty, responsibility, empathy, and love for the homeland with noble morals amidst the challenges of globalization.